2020
DOI: 10.1212/wnl.0000000000008817
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal change in regional brain volumes with exposure to repetitive head impacts

Abstract: ObjectiveThis study tests the hypothesis that certain MRI-based regional brain volumes will show reductions over time in a cohort exposed to repetitive head impacts (RHI).MethodsParticipants were drawn from the Professional Fighters Brain Health Study, a longitudinal observational study of professional fighters and controls. Participants underwent annual 3T brain MRI, computerized cognitive testing, and blood sampling for determination of neurofilament light (NfL) and tau levels. Yearly change in regional brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 35 publications
5
42
0
2
Order By: Relevance
“…These affected dFC still minimally demonstrate a medium effect size of | d | = 0.46. Both weaker sFC and structural damages have been observed among these regions from the current and previous reports ( 18 , 55 ). Therefore, overall, from our analysis, it can only be concluded that dFC measure of temporal variations across all windows in the sliding-window approach might not be sensitive enough to uncover significant between-group differences in fighters with repetitive head trauma.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These affected dFC still minimally demonstrate a medium effect size of | d | = 0.46. Both weaker sFC and structural damages have been observed among these regions from the current and previous reports ( 18 , 55 ). Therefore, overall, from our analysis, it can only be concluded that dFC measure of temporal variations across all windows in the sliding-window approach might not be sensitive enough to uncover significant between-group differences in fighters with repetitive head trauma.…”
Section: Discussionsupporting
confidence: 73%
“…The Professional Fighters Brain Health Study (PFBHS) launched at our center in 2011 ( 17 ) has focused on investigating brain changes related to repetitive head trauma and their associations with clinical and neuropsychological deficits in active professional fighters. Specifically, in PFBHS, structural MRI studies have revealed both cross-sectional and longitudinal brain volumes loss in fighters ( 18 ); and in a subset of fighters with neuropsychological impairments, abnormal white matter microstructural organization ( 19 ) and white matter topological reorganizations ( 20 ) have been observed with diffusion-weighted MRI studies.…”
Section: Introductionmentioning
confidence: 99%
“…This often means an AD diagnosis can be missed or delayed for years 60 . The impact is even more dramatic on the AD drug development pipeline which has seen significant bottlenecks in recruitment for early stage trials and studies composed of largely homogeneous populations 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of composite measures as endpoints in clinical trials have been encouraged by the Food and Drug Administration (FDA) and European Medical Agency (EMA) provided that the measures are carefully designed, are relevant to existing tools for which historical evidence exists, and are validated in independent prospective cohorts (20,21). Given that the RHICI is based on data derived from commonly used neuropsychological tools, the rst two requirements are met.…”
Section: Discussionmentioning
confidence: 99%